The determinants of financial development in five selected Asean countries / Nursyasya Emira Mohd Nazlan and Nur Fazida Fadzil - Mohd Nazlan, Nursyasya Emira; Fadzil, Nur Fazida (Faculty of Business and Management, 2019)
This study uses secondary data from 1995 until 2017 to analyse the pattern of Financial Development in five selected ASEAN countries and the factor that influence it. The economic study focuses on Government Expenditure, Trade Openness, Gross Domestic Product and Investment. Apart from that, the other objective of this research is to determine the determinants of the financial development in five selected ASEAN countries which are Malaysia, Indonesia, Thailand, Singapore, and Vietnam. There are several methods of analysis were used to analyse the data which are Panel Unit Root Test, Correlation Analysis, Regression Analysis, Autocorrelation, and Panel Regression Random Effect. The result proved that there has a positive relationship between factors that influencing Government Expenditure, Investments, Trade Openness and GDP towards the financial development in five selected ASEAN countries.